Reinforcement of new and existing reinforced concrete beams with fiber-reinforced polymer bars and sheets – A numerical analysis. (June 2022) - Aragão Almeida Júnior, Sálvio; Parvin, Azadeh
Abstract: Due to its durability and corrosion resistance, fiber-reinforced polymer (FRP) has become more readily adopted as reinforcement in new construction or existing concrete structures. With the increasing use of FRP reinforced members, the addition of new construction materials has been explored which requires investigation for their safe implementation. The significance of this study is to shed light on the response of newly-constructed and retrofitted simply-supported and continuous concrete beams reinforced with traditional FRP in various practical scenarios as compared to counterpart beams reinforced with steel bars and beams made with non-conventional materials. The parameters considered include the effects of environmental exposure, loading conditions, the addition of externally bonded FRP, and concrete type on the beams. Beams cast with normal-strength concrete and reinforced with steel and conventional FRP materials, such as carbon and glass fibers, were compared to beams cast with ultra-high-performance fiber-reinforced concrete and reinforced with basalt fibers. The results indicate that the use of these non-conventional materials can be advantageous in a number of scenarios by improving the beams' performance in terms of load and displacement responses.